2017
DOI: 10.1007/s40203-017-0034-0
|View full text |Cite
|
Sign up to set email alerts
|

Molecular docking analysis of curcumin analogues against kinase domain of ALK5

Abstract: During metastasis, cancer cells transcend from primary site to normal cells area upon attaining epithelial to mesenchymal transition (EMT) causing malignant cancer disease. Increased expression of TGF-β and its receptor ALK5 is an important hallmark of malignant cancer. In the present study, efficacy of curcumin and its analogues as inhibitors of ALK5 (TGFβR-I) receptor was evaluated using in silico approaches. A total of 142 curcumin analogues and curcumin were retrieved from peer reviewed literature and cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 45 publications
0
17
0
Order By: Relevance
“…PreADMET reveals that investigated COs are not inhibitors of the P-glycoprotein and outcomes values for the blood brain barrier penetration that are lower than 0.1 that correspond to a low absorbance to central nervous system (Aswathy et al, 2018). The PPB binding assessment (percentage of drug bound in plasma protein) reveals that investigated COs exhibit low binding energy with plasma proteins (PPB<90%) (Kandagalla et al, 2017) with the exception of the oligomer 6D that shows a high binding energy to plasma proteins (93.384%). SwissADME predicts that investigated compounds are not able to penetrate the blood brain barrier and are considered as substrates of P-glycoprotein.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…PreADMET reveals that investigated COs are not inhibitors of the P-glycoprotein and outcomes values for the blood brain barrier penetration that are lower than 0.1 that correspond to a low absorbance to central nervous system (Aswathy et al, 2018). The PPB binding assessment (percentage of drug bound in plasma protein) reveals that investigated COs exhibit low binding energy with plasma proteins (PPB<90%) (Kandagalla et al, 2017) with the exception of the oligomer 6D that shows a high binding energy to plasma proteins (93.384%). SwissADME predicts that investigated compounds are not able to penetrate the blood brain barrier and are considered as substrates of P-glycoprotein.…”
Section: Resultsmentioning
confidence: 99%
“…The action of chemicals depends on their interactions with plasma proteins, with unbound molecules usually reflecting better interactions with their targets and influencing the efficacy of the molecules (Kandagalla et al, 2017). All computational facilities that we have used reveal that COs considered in this study exhibit low potential to bind to plasma proteins.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to TGF-β signaling pathway, curcumin is able to suppress receptors in this pathway. Curcumin and its derivatives inhibit ALK5 to down-regulate migration and invasion of cancer cells ( Kandagalla et al, 2017 ).…”
Section: Curcumin and Transforming Growth Factor-beta In Different DImentioning
confidence: 99%
“…The lowest binding energy results were considered for further postdocking analysis. 55 The top-possible 5 phytoconstituents with the best docking score of Aβ and AChE were screened further for their drug-likeness through the admetSAR prediction, which revealed that 2 out of the 5 compounds tested for Aβ target; that is, 1-heneicosanol and N-nonadecanol-1. These compounds do not have carcinogenicity and have better BBB permeation, intestinal absorption, and less oral toxicity.…”
Section: Discussionmentioning
confidence: 99%